Effects of liraglutide and semaglutide on stroke subtypes in patients with type 2 diabetes: a post hoc analysis of the LEADER, SUSTAIN 6 and PIONEER 6 trials. (25th November 2020) - Strain, W.D; Holst, A.G; Rasmussen, S; Saevereid, H.A; James, M.A
Abstract: Introduction: Diabetes is an independent risk factor for stroke, with approximately a two-fold excess risk in people with versus those without diabetes. Accumulating evidence suggests glucagon-like peptide-1 (GLP-1) analogues (including liraglutide and semaglutide) may reduce the risk of stroke in patients with type 2 diabetes (T2D). Purpose: We examined the effect of liraglutide and semaglutide on stroke and its subtypes based on pooled data from LEADER, SUSTAIN 6 and PIONEER 6. Methods: LEADER (NCT01179048), SUSTAIN 6 (NCT01720446) and PIONEER 6 (NCT02692716) were global randomised cardiovascular (CV) outcomes trials of liraglutide, subcutaneous semaglutide and oral semaglutide, respectively, in patients with T2D at high CV risk. In this post hoc analysis, we evaluated the effect of these GLP-1 analogue treatments (pooled) on time to first occurrence of all strokes and subtypes of stroke. Ischaemic stroke was subcategorised according to the TOAST classification, based on aetiology by an external blinded reviewer. A Cox proportional hazards model stratified by trial with pooled treatment as a factor was used to examine treatment effects. Results: Across the three trials, 216/7907 (2.7%) patients in the GLP-1 analogue group and 262/7913 (3.3%) in the placebo group had a stroke. The risk of first occurrence of all strokes was significantly reduced in the GLP-1 analogue versus placebo group (HR 0.82, 95% CI 0.68–0.98; p=0.030). Treatment effects were consistent across stroke subtypes: ischaemic (HR 0.84, 95% CI 0.69–1.02; p=0.08), haemorrhagic (HR 0.72, 95% CI 0.42–1.22; p=0.22) and undetermined (HR 0.71, 95% CI 0.32–1.60; p=0.41; Figure 1). Across TOAST subcategories, there was a trend that GLP-1 analogue treatment had the greatest benefit versus placebo in small vessel occlusion strokes compared with large artery disease or cardioembolic strokes; however, no statistically significant effects were found in any subcategory. Conclusion: In this post hoc analysis of the LEADER, SUSTAIN 6 and PIONEER 6 trials, GLP-1 analogue treatment reduced the risk of stroke in patients with T2D and high CV risk, with an indication using TOAST criteria of the strongest effect on stroke caused by small vessel occlusion. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Novo Nordisk A/S. WDS is supported by the NIHR Exeter Clinical Research Facility. MAJ is supported by the NIHR SW Peninsula Applied Research Collaboration. This abstract does not necessarily reflect the views of the NIHR, the Exeter Clinical Research Facility, the NHS or the UK Department of Health.